FACTORS INFLUENCING SKELETAL MUSCLE REMODELLING WITH LOADING - Mcleod, Jonathan (My University, 2023)
Skeletal muscle is a plastic tissue that can adapt to several stimuli by changing its metabolic and contractile properties. Increased skeletal muscle mass can be brought on by loading through resistance exercise training, whereas decreased skeletal muscle mass can be brought on by reducing skeletal muscle contractile activity. Rates of muscle protein synthesis can be influenced by several factors broadly categorized as external or internal system variables. External system variables are environmental perturbations indispensable for activating internal system variables. Internal system variables are local, skeletal muscle-specific, biological processes that mechanistically underpin skeletal muscle adaptations. The overarching objective of the experiments conducted as part of this thesis was to discover the influence of external variables (resistance training program variables) and internal variables (long noncoding RNA) on skeletal muscle adaptations and characterize changes in skeletal muscle protein synthesis under various scenarios. In studies 1 and 2, we used systematic review and network meta-analytical methodology and discovered that resistance exercise training load, volume, and weekly frequency were important determinants of skeletal muscle adaptations. As an internal variable, the long-noncoding transcriptome is poorly characterized in skeletal muscle biology, and for study 3, we used five independent exercise studies to identify a novel long-noncoding RNA signature associated with resistance exercise-induced changes in lean mass. Lastly, in study 4, we characterized integrated rates of bulk muscle protein synthesis under distinct loading states in young, healthy men. We found that 14 days of single-leg immobilization was sufficient to induce rapid declines in muscle protein synthesis, whereas 4 sessions of resistance exercise increased muscle protein synthesis. Taken together, the findings of this thesis contribute substantially to our understanding the role of external and internal variables on skeletal muscle remodelling.